Guru Sebagai Supervisor: Kajian Pustaka tentang Membangun Pembelajaran Kreatif dan Inovatif - Irmawati, Irmawati (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
The rapid digital transformation and the implementation of Kurikulum Merdeka in Indonesia necessitate a paradigm shift in education. This study aims to analyze the teacher's role as a supervisor in fostering creative and innovative learning environments. Using a qualitative library research method with content analysis, this study synthesized literature from 2019 to 2025. The results indicate that the teacher's supervisory role has evolved from rigid administrative oversight to a formative-interactive process that integrates digital mentoring. Effective strategies include the implementation of Project-Based Learning (PjBL) and the integration of immersive technologies like VR/AR. Furthermore, addressing challenges such as high administrative workloads and resistance to change requires continuous professional training and resource optimization. In conclusion, teacher supervision acts as a vital catalyst for educational transformation in the Society 5.0 era, supporting national goals for higher student competency.